Kepemimpinan Inspiratif Menurut Imam Al-Ghazali: Mengembangkan Motivasi Spiritual dan Moral - Solich, Moch (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2024)
Abstract Leadership is a key factor in achieving organizational goals, particularly in motivating members to perform effectively. This study explores the leadership strategies of Imam Al-Ghazali, focusing on spiritual and moral dimensions to enhance motivation. Employing a qualitative library research method, the study analyzes primary texts such as Ihya Ulumuddin and Nasihat al-Muluk. The results reveal that leadership, according to Al-Ghazali, is rooted in ethical responsibility, justice, and wisdom. His principles of motivation emphasize aligning actions with the ultimate purpose of life—seeking Allah's pleasure—while balancing material and spiritual needs. Furthermore, Al-Ghazali outlines strategies such as leading by example (uswatun hasanah), instilling values of honesty and piety, fostering harmony, and providing rewards that strengthen spiritual commitment. This study concludes that Al-Ghazali’s leadership framework offers a holistic approach, integrating spiritual growth with social and organizational welfare, and is relevant for contemporary leadership practices aiming to inspire and empower individuals.